MSC-EVs and UCB-EVs promote skin wound healing and spatial transcriptome analysis - Ruonan Li; Haotian Wang; Xiaolong Wang; Yanbin Yang; Kai Zhong; Xuemei Zhang; Heping Li (Scientific Reports)
Abstract Extracellular vesicles (EVs) are important paracrine mediators derived from various cells and biological fluids, including plasma, that are capable of inducing regenerative effects by transferring bioactive molecules such as microRNAs (miRNAs). This study investigated the effect of mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) isolated from umbilical cord blood and human umbilical cord plasma-derived extracellular vesicles (UCB-EVs) on wound healing and scar formation reduction. Spatial transcriptomics (ST) was used to study the effects of MSC-EVs and UCB-EVs on the heterogeneity of major cell types and wound healing pathways in mouse skin tissue. MSC-EVs and UCB-EVs were isolated using ultracentrifugation and identified using transmission electron microscopy, nanoparticle tracking analysis, and western blot. The effects of MSC-EVs and UCB-EVs on human dermal fibroblast-adult cell (HDF-a) migration and proliferation were evaluated using cell scratch assays, cell migration assays, and cell proliferation assays. In vivo, MSC-EVs and UCB-EVs were injected around full-cut wounds to evaluate their efficacy of wound healing by measuring wound closure rates and scar width and performing histological analysis. ST was performed on skin tissue samples from mice in each group after wound healing to analyze the heterogeneity of major cell types compared with the control group and investigate potential mechanisms affecting wound healing and scar formation. In vitro experiments demonstrated that MSC-EVs and UCB-EVs promoted the proliferation and migration of HDF-a cells. Local injection of MSC-EVs and UCB-EVs into the periphery of a mouse skin wound accelerated re-epithelialization, promoted wound healing, and reduced scar width. ST analysis of skin tissue from each group after wound healing revealed that MSC-EVs and UCB-EVs reduced the relative expression of marker genes in myofibroblasts, regulated wound healing, and decreased scar formation by reducing the expression of the TGF-β signaling pathway and increasing the expression of the Wnt signaling pathway. The results suggest that MSC-EVs and UCB-EVs play a significant role in the activity of cord blood plasma-derived mesenchymal stem cells and cord blood plasma. They can be considered promising new agents for promoting skin wound healing.